The right to privacy in relation to the mass media: An analysis of the Malaysian position / Nurul Azureen Ahsin … [et al.] - Ahsin, Nurul Azureen; Yaakub, Mohamad Rizal; Yaacub, Norizan; Anuar, Muhammad Amin (Faculty of Law, 2011)
The right of privacy has been the subject of dispute for centuries. However there was little attempt made by the legislative body to clearly define the right of privacy, especially in cases relating to the mass media. Whenever an issue touches on the media's invasion of personal privacy, the aggrieved parties have to resort to the common law tort of defamation, or any existing and enforceable written law such as the Data Protection Act, the Penal Code or any other statutes which are barely relates to the case in question. For example, the recent Data Protection Act 2010 mainly focuses on a person's right to privacy in relation to his personal data from being misused by the authority. Thus, this research aims to identify the loopholes of the existing privacy law in Malaysia and recommend the appropriate measures to be taken to protect the rights of a person to privacy. Throughout the research, we look into all approaches in relation to the protection of privacy that are practised in the United Kingdom, the United States of America, as well as several other countries and how it is applied in dealing with cases relating to breach of privacy. We also found that various approaches practised by some countries are quite different from the practise in Malaysia. Hence, we believe that there is a very large room for improvement in the privacy law pertaining to the mass media in Malaysia. Based on the research conducted, it is concluded that the rights to privacy should be legally recognized in Malaysia. In order for this recognition to be officialised, specific steps should be taken to enact a law governing the right of privacy. This law should be enforced by the executive, and upheld by the judiciary body to ensure that a person's right to privacy is upheld. It is hoped that by conducting this research, we can bring about a better and more effective protection in safeguarding one's privacy.